Decoding Consumer Choices: How Brand Image and Pricing Form Purchasing Behavior? - Yuaniko, Yuaniko; Caniago, Melinda Syafri (SAN Scientific, 2024)
This study analyzes the impact of brand image and price on consumer purchasing decisions for Aice ice cream in Bekasi City. In a competitive market like the ice cream industry, both brand image and price are essential factors influencing purchasing behavior. Data were gathered from 100 Aice consumers through a questionnaire survey, and multiple linear regression analysis was employed to assess the effect of brand image and price (independent variables) on purchasing decisions (dependent variable). Results show that both brand image and price significantly and positively influence purchasing decisions. This suggests that to enhance consumer interest, companies should focus on maintaining a strong brand image and offering competitive pricing. The findings provide valuable insights for managers and marketers in developing effective marketing strategies. If brand image indeed strongly affects purchasing choices, companies should prioritize consistent branding and communication efforts to reinforce their brand image. This study aims to assist companies in designing more targeted strategies to increase consumer demand and competitiveness in the ice cream sector.